The Effect of Using Scaffolding and Woods Models on the Development of Science Process Skills of Female Nineth Graders - Shakkah, Suzan M.; Khataibeh, Abdullah M. (Dirasat: Educational Sciences, 2020)
This study aimed at investigating the effect of using Scaffolding and Woods models on the development of science process skills of female nineth graders. The sample consisted of (58) female students from the ninth grade, distributed into three groups. The first experimental group was taught using educational scaffolding model. The second experimental group was taught using the Woods model. The third group was a control group. The test of the science process skills was a multiple-choice test, which consisted of (30) items. The results showed that there were statistically significant differences at the level of (α = 0.05) between the experimental groups and the control group due to the teaching model for the benefit of students of two experimental groups for all dimensions. The study recommended using scaffolding and Woods models for the development of science processes among students.